Sports Development of Top Terme Topusko - Azinović, Toni; Barišić, Ema; Bičo, Armin (Strategije za održivi i ruralni razvoj gradova Siska, Petrinje i Hrvatske Kostajnice i općina Majur i Topusko, 2025)
This research focuses on Top Terme Topusko, a thermal spa located in Sisak-Moslavina County, with particular emphasis on its potential for sports tourism development. The facility possesses sufficient accommodation capacity to support sports tourism; however, its infrastructure requires renovation to align with contemporary sports trends. A SWOT analysis was conducted to identify key strengths, weaknesses, opportunities, and threats related to further development. The findings suggest that the current extensive range of services should be streamlined and strategically oriented towards a few priority areas, with sports tourism as a central focus. Based on the existing infrastructure, the study proposes priority offerings that could enhance the centre’s competitiveness. Furthermore, the development of complementary activities, such as thematic routes, may contribute not only to the attractiveness of the spa but also to the broader municipality by encouraging tourist mobility and engagement with local products and experiences. This approach aligns with sustainable development principles and reflects contemporary trends that position local communities and resources at the core of tourism offerings.